Correlations between Health Belief and 3E 2S Health Behaviors of Elderly in Taejew Community Tungwatdorn Satorn Bangkok Thailand - Punthasee, Pornsiri; Srisawad, Kanjana (Journal of health and health management, 2020)
The objectives of this descriptive correlational research were to study the relationship between health belief perception and 3E 2S (Eating, Exercise, Emotion, Smoking, Spirits) health behaviors among elderly in Taejew Community Tungwatdorn Satorn Bangkok Thailand. The 134 samples were purposive sampling. The research tool was questionnaire consists of personal data, health belief and 3E 2S health behaviors. Data were analyzed by using descriptive statistics, chi-square test and Pearson product moment correlation coefficient. The results revealed that the overall health perception were high level ( =4.42, SD=.40) and the highest level is perceived susceptibility ( = 4.65, SD=.53). The overall 3E 2S health behaviors were high level as well ( =4.34, SD = .70) and the highest level is non smoking ( = 4.75, SD=.90). It was also found that the elderly, who had different marital status and income, were statistical significance different 3E 2S health behaviors (p<.05). Besides the 3E 2S health behaviors were statistical significance positive associated with the overall health perception (r=.26, p<.01). and perceived benefits (r= .30 , p<.01) but were negative associated with perceived barrier to disease prevention (r= -.29, p<.01).